Analysis of electronic parameters of nanostructure copper doped cadmium oxide/p-silicon heterojunction - Karatas, Sukru; Yakuphanoğlu, Fahrettin (Elsevier Science Sa, 2012)
The nanostructure Cu-doped CdO thin film was grown on p-type silicon substrate by sol-gel method. An Al/Cu doped CdO/p-Si heterojunction diode was fabricated. The values of ideality factor and barrier height for the Al/n-type CdO/p-Si heterojunction were obtained as 5.99 and 0.69 eV, respectively. A modified Norde function combined with conventional forward I-V method was used to extract the junction parameters including the ideality factor, barrier height and series resistance. Norde function was compared with the Cheung functions and it is seen that there is a good agreement with both method for the series resistance values. Furthermore, the interface state density (N-SS) as a function of energy distribution (E-SS - E-V) was extracted from the forward-bias I-V measurements by taking into account the bias dependence of the effective barrier height and series resistance. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: CdO thin film; Electrical properties; Interfaces; Sol-gel method